Neisseria meningitidis Serogroup X in Sub-Saharan Africa - Alain Agnememel (Emerging Infectious Diseases, 2016)
The epidemiology of meningococcal disease varies by geography and time. Whole-genome sequencing of Neisseria meningitidis serogroup X isolates from sub-Saharan Africa and Europe showed that serogroup X emergence in sub-Saharan Africa resulted from expansion of particular variants within clonal complex 181. Virulence of these isolates in experimental mouse models was high.